THE USED OF MULTIMEDIA IN ENGLISH LANGUAGE TEACHING; (A CASE STUDY AT SMP NEGERI 2 MESJID RAYA, ACEH BESAR) - Rahmi, Regina (Getsempena English Education Journal, 2014)
Learning and teaching a foreign language needs a lot of patience, energy, time, creativity and competence. The success of the teaching and learning of foreign language skills including English is determined by a number of factors such as students, teachers, teaching methods, techniques, and instructional Multimedia. English teaching Multimedia are very important for teacher to help students acquire new concept of the skills and language competences. English has been taught at primary level due to its important role. English teachers in this level need more knowledge about children in mastering English. It is done because children have certain characteristics that differ from adult learners. There are still many fascinating discussions that might be interesting to find out the real situation in the implementation of Multimedia in English language teaching, especially to children. This study which was conducted at Elementary School Islam Laboratorium Neuhen, Mesjid Raya is intended to figure out how the use of Multimedia in English language teaching to the first levels. The study employed case study research design. The population was 44 and the sample was taken by using nonprobability sample, convenience sampling, was an English teacher. The research problem is âhow does the teacher implement Multimedia in teaching English? The data were collected by using instruments, namely: observation checklist sheets, questionnaire sheet, interview guidelines, and documentations. Based on the data analysis, it was found that the English teacher at SMP Negeri 2 Mesjid Raya used multimedia in English language teaching. There is some variable which observe by the researcher, there are: Computer, Internet, Print text, and Movie. According to the studentsâ competencies, the teacher build up new atmosphere in teaching learning process by using pint text in reading, speaking, writing and vocabulary. The used of movie help the students in all competencies, such as reading, speaking, listening, writing and vocabulary teaching learning process. Â Key words: English Language, Teaching, Multimedia